THE FLUCTUATIONS IN THE IRAS DISTRIBUTION - Shatsova, R. B.; Anisimova, G. B. (Одеські астрономічні публікації, 2017)
The great fluctuations in the infrared sky are situated along the meridians of Universal Sky Net. It is related also to the large structures. So the edge of the zone of avoidance of galaxies over IRAS60 and IRAS100 for long extension coincides to the Γ-meridian, perpendicular to the ecliptic E. The Large Magellanic Cloud is situated near the southern pole of ecliptic. The IR radiation of the zodiacal belt, discovered by Hauser, is confirmed. Perhaps, it is obliged not only and not so much to a zodiacal light of the Solar system.